2012
DOI: 10.4315/0362-028x.jfp-11-258
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Salmonella, Listeria monocytogenes, Escherichia coli O157:H7, and Staphylococcal Enterotoxin in Two Types of Mexican Fresh Cheeses

Abstract: Handcrafted fresh cheeses are popular among consumers in Mexico. However, unsafe raw materials and inadequate food safety practices during cheese manufacture and preservation make them a potential public health risk. The incidence of Salmonella, Listeria, Escherichia coli O157:H7, and staphylococcal enterotoxin was analyzed in two types of fresh cheese (panela and adobera) commonly marketed in Mexico. A total of 200 samples, 100 panela and 100 adobera, were acquired from 100 wholesale milk product distributor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 19 publications
0
40
0
1
Order By: Relevance
“…This practice has repeatedly resulted in outbreaks associated with queso fresco and other Mexican-style cheeses made from unpasteurized milk (Linnan et al , 1988; Altekruse et al , 1998; Cody et al , 1999; Villar et al , 1999; MacDonald et al , 2005; Centers for Disease Control and Prevention, 2008). One study found that 46% of cheese samples imported from Mexico were contaminated with Salmonella, E. coli O157:H7, or Listeria, in addition to frequent contamination by debris and insects (Torres-Vitela et al , 2012). Surveys of imported cheeses have found higher levels of pathogens in cheeses imported from Mexico and Central America than other regions (D’Amico and Donnelly, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This practice has repeatedly resulted in outbreaks associated with queso fresco and other Mexican-style cheeses made from unpasteurized milk (Linnan et al , 1988; Altekruse et al , 1998; Cody et al , 1999; Villar et al , 1999; MacDonald et al , 2005; Centers for Disease Control and Prevention, 2008). One study found that 46% of cheese samples imported from Mexico were contaminated with Salmonella, E. coli O157:H7, or Listeria, in addition to frequent contamination by debris and insects (Torres-Vitela et al , 2012). Surveys of imported cheeses have found higher levels of pathogens in cheeses imported from Mexico and Central America than other regions (D’Amico and Donnelly, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, 41 people across five southwestern states of the United Stateswere afflicted by food poisoning due to Escherichia coli O157:H7 and majority of them reported the consumption of Gouda cheese (McCollum et al, 2012). Moreover, Torres-Vitela et al (2012) observed that high incidence of E. coli O157:H7, Salmonella, Listeria, and staphylococci occurrence in cheeses that are commonly marketed in Mexico. Food safety is undoubtedly the important priority for the food industry as well as consumers.…”
Section: Introductionmentioning
confidence: 97%
“…For several years before 2009, surveys and enhanced surveillance operations conducted by the FDA, the CBP, and state health agencies at noncommercial ports of entry (POE) along the United States–Mexico border have revealed high violation rates for raw milk cheeses and evidence of pathogens in imported QF, including Salmonella , Escherichia coli O157:H7, Listeria spp., and Mycobacterium bovis ( 14, 16, 18, 21, 29 ) . QF-associated disease is more common in Hispanic populations, among whom pregnant women and the elderly appear to be at increased risk ( 24, 27 ) .…”
mentioning
confidence: 99%
“…QF-associated disease is more common in Hispanic populations, among whom pregnant women and the elderly appear to be at increased risk ( 24, 27 ) . Outbreaks and sporadic cases of salmonellosis, listeriosis, brucellosis, and M. bovis infections have been frequently associated with consumption of QF in Hispanic communities in California and throughout the United States ( 4–9, 11, 19, 25, 29 ) .…”
mentioning
confidence: 99%